The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0041-1729169
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients with Isolated Distal Deep Vein Thrombosis versus Proximal Deep Vein Thrombosis or Pulmonary Embolism: RE-COVERY DVT/PE Study

Abstract: Isolated distal deep vein thrombosis (IDDVT) is presumed to be more benign than proximal DVT (PDVT) or pulmonary embolism (PE), suggesting a need for different management approaches. This subgroup analysis of the RE-COVERY DVT/PE global, observational study investigated patient characteristics, hospitalization details, and anticoagulant therapy in patients with IDDVT in real-world settings in 34 countries enrolled from January 2016 to May 2017. Data were analyzed descriptively according to the type and locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“… 6 7 However, studies describing clinical practice patterns report that almost all patients with isolated distal DVT receive anticoagulant treatment, with a proportion similar to that of patients with proximal DVT or pulmonary embolism. 8 9 11 12 Furthermore, in a study comparing outcomes among patients with isolated distal DVT stratified by management strategy, recurrence rates were statistically significantly lower in patients receiving anticoagulants than in those managed with surveillance ultrasonography only, and the net clinical benefit, including major bleeding events, clearly favoured anticoagulant treatment. 13 The actual difference between the management of isolated distal DVT and proximal DVT or pulmonary embolism is the duration of treatment, which tends to be shorter, with many patients with isolated distal DVT treated for 4-6 weeks 3 5 14 and fewer patients with isolated distal DVT treated for more than three months compared with patients with proximal DVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 7 However, studies describing clinical practice patterns report that almost all patients with isolated distal DVT receive anticoagulant treatment, with a proportion similar to that of patients with proximal DVT or pulmonary embolism. 8 9 11 12 Furthermore, in a study comparing outcomes among patients with isolated distal DVT stratified by management strategy, recurrence rates were statistically significantly lower in patients receiving anticoagulants than in those managed with surveillance ultrasonography only, and the net clinical benefit, including major bleeding events, clearly favoured anticoagulant treatment. 13 The actual difference between the management of isolated distal DVT and proximal DVT or pulmonary embolism is the duration of treatment, which tends to be shorter, with many patients with isolated distal DVT treated for 4-6 weeks 3 5 14 and fewer patients with isolated distal DVT treated for more than three months compared with patients with proximal DVT.…”
Section: Discussionmentioning
confidence: 99%
“… 13 The actual difference between the management of isolated distal DVT and proximal DVT or pulmonary embolism is the duration of treatment, which tends to be shorter, with many patients with isolated distal DVT treated for 4-6 weeks 3 5 14 and fewer patients with isolated distal DVT treated for more than three months compared with patients with proximal DVT. 8 9 15 …”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, patients with ICDVT had a lower risk of recurrence than patients with proximal DVT 31 . A recent multicenter and observational study showed that cumulative VTE recurrence was 4.8 times higher in patients with proximal DVT than in patients with distal DVT after 5 years of follow‐up 32 . In addition, bilateral isolated DVT has a worse prognosis, with more frequent recurrence, higher mortality, and a more frequent association with malignant tumors 33 , 34 , 35 , 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Moving on to the adult population, Schellong et al are here reporting data on isolated distal DVT in comparison with proximal DVT from a registry study with 6,095 patients. 10 The investigators found differences in the demography and risk factors between patients with distal DVT compared with proximal DVT and/or PE. There were also differences in location of diagnosis and initial clinical management.…”
Section: Robert Louis Stevenson 1850-1894mentioning
confidence: 98%